2015
DOI: 10.1111/pbi.12442
|View full text |Cite
|
Sign up to set email alerts
|

Are all GMOs the same? Consumer acceptance of cisgenic rice in India

Abstract: SummaryIndia has more than 215 million food-insecure people, many of whom are farmers. Genetically modified (GM) crops have the potential to alleviate this problem by increasing food supplies and strengthening farmer livelihoods. For this to occur, two factors are critical: (i) a change in the regulatory status of GM crops, and (ii) consumer acceptance of GM foods. There are generally two classifications of GM crops based on how they are bred: cisgenically bred, containing only DNA sequences from sexually comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“…This result shows that consumers are willing to pay US$13.75 more per 5kg bag, a premium of 275%, for a rice variety that was produced with no fungicide. These findings are consistent with those found in similar studies by Delwaide et al (2015) and Shew et al (2016) in the European Union and India, respectively. Their research, which was also hypothetical, shows that consumers in France and India are willing to pay a premium of 667% and 486%, respectively for rice that is labeled, EB, as compared to conventional rice.…”
Section: Interval Regression Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result shows that consumers are willing to pay US$13.75 more per 5kg bag, a premium of 275%, for a rice variety that was produced with no fungicide. These findings are consistent with those found in similar studies by Delwaide et al (2015) and Shew et al (2016) in the European Union and India, respectively. Their research, which was also hypothetical, shows that consumers in France and India are willing to pay a premium of 667% and 486%, respectively for rice that is labeled, EB, as compared to conventional rice.…”
Section: Interval Regression Resultssupporting
confidence: 93%
“…Contrary to the case of rice that is labeled, EB, and in line with the WTP's for EB estimated for France and India by Delwaide et al (2015) and Shew et al (2016), the positive sign on these estimates indicates that consumers require a discount of 108% or 325% for a rice that is labeled, CIS or GM. Consequently, these discounts translates to willingness-to-accept estimates of US$4.75 and US$14.94 for rice labeled as CIS or GM, respectively.…”
Section: Interval Regression Resultsmentioning
confidence: 64%
“…Similar results were found in experimental auctions in the US (Colson et al ., ). A survey on Indian consumers found that respondents did not value cisgenic and transgenic rice differently, but there was a positive WTP for no‐fungicide, provided by the cisgenic and transgenic rice types (Shew et al ., ).…”
Section: Previous Workmentioning
confidence: 97%
“…GM cisgenic/intragenic technology only introduces new genes from the same or sexually compatible donors into a host plant and thus should have been able to address some of the public concerns about the GM transgenic technology. Multiple studies indicate that consumer acceptance of the GM cisgenic/intragenic technology is greater than that for the GM transgenic technology (Colson & Huffman, 2011; Delwaide et al., 2015; Edenbrandt, Gamborg, & Thorsen, 2018; Shew et al., 2016). It should be noted that the efficiency and specificity of the insertion of exogenous genes in a plant genome are generally low under GM technologies (Ishii & Araki, 2016).…”
Section: Introductionmentioning
confidence: 99%